Iron-Catalyzed Direct Diazidation for a Broad Range of Olefins - Yuan, Yong-An; Lu, Deng-Fu; Chen, Yun-Rong; Xu, Hao (Angewandte Chemie International Edition, 2016)
Reported herein is a new iron‐catalyzed diastereoselective olefin diazidation reaction which occurs at room temperature (1–5 mol % of catalysts and d.r. values of up to >20:1). This method tolerates a broad range of both unfunctionalized and highly functionalized olefins, including those that are incompatible with existing methods. It also provides a convenient approach to vicinal primary diamines as well as other synthetically valuable nitrogen‐containing building blocks which are difficult to obtain with alternative methods. Preliminary mechanistic studies suggest that the reaction may proceed through a new mechanistic pathway in which both Lewis acid activation and iron‐enabled redox‐catalysis are crucial for selective azido‐group transfer. With iron hand: The title reaction proceeds at room temperature and tolerates a broad range of both unfunctionalized and highly functionalized olefins. It also provides a convenient synthetic approach to a variety of nitrogen‐containing building blocks. Preliminary mechanistic studies suggest both Lewis acid activation and iron‐enabled redox catalysis are crucial for the selective azido‐group transfer.